The Sacred Grammar of Time: Critical Discourse Analysis and Theology in ‎Reading World History - Iskandarsyah Siregar; Awang Azman Awang Pawi (JPI: Jurnal Pustaka Indonesia, 2026)
This study examines how contemporary world history is linguistically and theologically constructed through discourses of crisis, transition, risk, misinformation, religious identity, and moral accountability. Using a qualitative-dominant mixed-method design, the study integrates Critical Discourse Analysis, corpus-assisted discourse analysis, and Islamic theological hermeneutics to analyze publicly accessible institutional, geopolitical, digital-governance, and religious-public texts published or updated between 2024 and 2026. The findings show that contemporary global discourse frames the present as unstable, the future as threatened, and historical change as a managerial problem of security, governance, and adaptation. At the same time, Islamic theological concepts such as sunnatullah, fitnah, ajal, qadar, ibrah, tabayyun, and akhirah provide a moral framework for interpreting time as an arena of human responsibility before God, society, and creation. This study proposes sacred temporal discourse analysis as an interdisciplinary framework for reading world history as a linguistic-theological formation in which language, ideology, power, memory, revelation, and moral imagination intersect. The implication is that contemporary global crises should not be understood only through political, technological, or risk-management perspectives, but also through ethical reflection on truth, justice, accountability, and civilizational responsibility.